Conceptual issues for screening in the genomic era – time for an update? (Epidemiology, Biostatistics, and Public Health, 2022)
screening from clinical testing remains strangely elusive. Although numerous definitions of screening have been suggested, there is considerable variation amongst them, leading to confusion and disagreement amongst clinicians and public health professionals alike. In light of developments in genomics, we emphasise the need to differentiate between opportunistic screening and clinical testing because of the differing prior probability of disease and thus ethical burden of responsibility placed upon the physician in each scenario. Screening requires higher standards, first because screening tests are performed in asymptomatic individuals, and second because these tests are generally offered to individuals who otherwise believe themselves to be healthy. All the other characteristics commonly invoked to describe screening – including the systematic use of a rapid test for risk stratification within a particular population – can be better categorised as either practical requirements or by-products of screening programmes rather than screening tests. Physicians need to appreciate the shifting moral burden placed upon them relating to clinical testing versus screening, and the differing legal obligations that may ensue.